Design and Creation of Electronic Teaching Aid for Effectiveness and Attractiveness of Education Increasing - Kováčik, Peter (Journal of Education, Technology and Computer Science, 2021)
The article analyses requirements of new methods of student education at the level of secondary school with professional electrical and electronic focus. It describes the creation of a new teaching aid that incites fantasy, concentration and motivation to create interesting things by self competence of students oriented to the electrical field of study. At the same time it orientates students towards unconventional ways of thinking and non orthodox solutions. Teaching aid exploits digital form that is attractive for young people with the aspiration to focus the attention of students to study professional knowledge.